2001
DOI: 10.1161/hc3301.092804
|View full text |Cite
|
Sign up to set email alerts
|

His Electrogram Alternans Reveal Dual-Wavefront Inputs Into and Longitudinal Dissociation Within the Bundle of His

Abstract: Background-His electrogram (HE) amplitude and morphology changes were observed in our previous studies during transition from "fast" to "slow" atrioventricular nodal (AVN) conduction. This phenomenon and its significance for the dual-AVN electrophysiology are not well recognized and have not been studied. Methods and Results-Experiments were performed on 17 healthy rabbit atrial-AVN preparations during standard programmed electrical pacing. HEs were mapped along the His bundle with roving surface electrodes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 26 publications
8
52
0
Order By: Relevance
“…In figure 2.6 an example of high-low IHE alternans recorded during experimental AF in rabbit heart preparation [44,45,46]. Successful SP modification prolonged the AV node ERP without changing the basic AV node conduction time, which is consistent with clinical SP ablation [3].…”
Section: Treatment Of Atrial Fibrillationsupporting
confidence: 57%
See 4 more Smart Citations
“…In figure 2.6 an example of high-low IHE alternans recorded during experimental AF in rabbit heart preparation [44,45,46]. Successful SP modification prolonged the AV node ERP without changing the basic AV node conduction time, which is consistent with clinical SP ablation [3].…”
Section: Treatment Of Atrial Fibrillationsupporting
confidence: 57%
“…In rabbit heart experiments it was shown that this index could be used to determine on a beat-by-beat basis during AF the AV node conduction pattern (i.e. though FP or SP) [44,45,46]. Specifically, a low amplitude inferior bundle of His electrogram (IHE) was associated with FP conduction, while high-amplitude IHE indicates SP conduction.…”
Section: Treatment Of Atrial Fibrillationmentioning
confidence: 99%
See 3 more Smart Citations